CARCASSES PIECES OF KAMPUNG UNGGUL BALITNAK (KUB) CHICKEN FED TURMERIC (Curcuma domestica Val.) EXTRACT THROUGH DRINKING WATER - A.S.A., Hasib; Siti, N.W.; Sukmawati, N.M.S. (Jurnal Peternakan Tropika, 2024)
The research aim to determining the effect of turmeric extract supplementation through drinking water on the carcass pieces of KUB chickens was conducted at the Farm of the Faculty of Animal Husbandry, Udayana University, located on Sesetan Main Road, Denpasar, Bali. The research duration was 8 weeks, from January 8 th , 2023, to March 5 th , 2023, using a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. Each replication consisted of two unsexed KUB chickens with an initial body weight of 58,34 ± 1,540 g. The treatments given were P0 (drinking water without turmeric extract), P1 (drinking water + 1% turmeric extract), P2 (drinking water + 2% turmeric extract), and P3 (drinking water + 3% turmeric extract). The variables observed were the percentage of breast, wing, back, thigh, and drum stick. The results showed that P0, P1, P2, and P3 treatments in drinking water did not have a significant effect (P>0.05) on the carcass cuts of KUB chickens. Based on the results, it can be concluded that turmeric extract supplementation up to 3% provides similar results to the carcass cuts of KUB chickens.